Structural aspects of the family of a pregnant woman with human papillomavirus - Moura, Ana Débora A.; Bezerra, Saiwori J.S.; Pinheiro, Ana Karina B.; Barroso, Maria Grasiela T. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: family can have many definitions as the consanguinity, the kinship and the affinity through marriage. Several factors influence its struc ture causing crisis, which include socio-political and economical, religious and cultural factors, such as violence, unemployment, diseases etc. Objec tive: to evaluate structural aspects of one family with carrier of Human Papilomavírus (HPV) assisted in a health service, based on the Calgary Model. Methods: descriptive exploratory study, with qualitative approach, using Calgary Model of family evaluation as theoretical reference. The subject of the research was a pregnant woman who had a lesion by HPV, assisted in a Centre of Secondary Attention in the approach to Sexually Transmitted Diseases (STD) from Fortaleza - CE. The data collection occured in January, 2007, through interviews and the instrument used was a semi-structured schedule. The speeches were transcribed with consequent execution of discussions and analyzed based on the pertinent literature, and presented through Genogram, Ecomap and family testimony. Results: in this study, we noticed that the disease did not interfere in the matrimonial relationship and in the development of the nuclear family (the couple); the pregnant presents a strong link with her extended family and the nuclear family has a closed family system, with little social interaction. Conclusion: Although the couple relates that there were no great repercussions with the discovery of HPV, the feeling of embarrassment, and fear of being rejected emerged, which confirm the existence of stigmas associated to STD.